The possibilities and limitations of organic fruit production - Dremák, Péter (Acta Agraria Debreceniensis, 2010)
In this review, direct and indirect technological elements of organic production are discussed. Today, there is a growing interest in production prepared without chemicals. We discuss the following issues: site selection, soil, rootstock and cultivar requirements, plant material, planting distances, crown formation, phytotechical operation, irrigation, soil tillage, soil covering and muchning, nutrition supply. Separate section deals with methods of plant protection.